(3QSGdI aj GdYed HGdGSWQdGHs - (3YHO GdQMef Hf YeQ Hf Sgd GdUhaj GdQGRqj, CHh GdMSjf,J (B376 (3g` s
(3ChdgG (B:s
(3ai TQM GdYed HGdcQI hhVYJ ai KdGK ebGdGJ s
(3BNQgG (B:s
(3GdTeS ai bUQ jhe ai GdSfI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B319 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B162s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B845s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs